2003
DOI: 10.1055/s-2003-37020
|View full text |Cite
|
Sign up to set email alerts
|

Variceal Bleeding and Portal Hypertension: Has There Been Any Progress in the Last 12 Months?

Abstract: A review of the literature on the management of esophagogastric varices published in the last 12 months shows that the data are still quite conflicting. In the primary and secondary prophylaxis of variceal bleeding, beta-blockers are still the mainstay of pharmacotherapy. Measurement of the hepatic portal venous pressure gradient is considered to be a reliable parameter for successful reduction of portal pressure using medical therapy. However, intolerance of propranolol requiring discontinuation of therapy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Once bleeding occurs, however, it becomes massive and leads to high mortality and re-bleeding rates. Some have suggested that EHI is superior to other therapeutic modalities for achieving hemostasis in actively bleeding GVs (87-100%) [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Once bleeding occurs, however, it becomes massive and leads to high mortality and re-bleeding rates. Some have suggested that EHI is superior to other therapeutic modalities for achieving hemostasis in actively bleeding GVs (87-100%) [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…When the injection is complete, the needle is removed from the varix, and normal saline is sprayed on the puncture site to allow the cyanoacrylate to solidify promptly. When removing the conduit for injection, it is better to wait for 20 seconds to allow adequate polymerization before removal, and during this time, the contents of the stomach should not be aspirated to prevent the channel lumen from becoming obstructed 41. If the cyanoacrylate content is too high, it could solidify within the conduit, impeding the injection, or it could solidify within the varix rapidly before the conduit is removed and impede the removal of the conduit.…”
Section: Endoscopic Hemostasis Of Acute Variceal Bleedingmentioning
confidence: 99%
“…30 31 Endoscopic therapy has been considered the mainstay of specific treatment for acute variceal bleeding 32 (provided that such facilities are available), with some authors emphasising the need for expert and rapid control of haemorrhage. 33 Although randomised trials of sclerotherapy 32 versus banding ligation have shown that ligation is more effective (pooled odds ratio (OR) 0.51; 95% CI 0.34 to 0.79) in controlling bleeding, 34 there is no statistical difference in survival. As placement of the banding device requires extubation after the diagnostic endoscopy and then reintubation, this probably increases the risks of endoscopy, but this has not been assessed formally.…”
Section: Acute Variceal Bleedingmentioning
confidence: 99%